Klatskin-Mimicking Lesions - Marinko Marušić (MDPI AG, 2021)
Altemeier-Klatskin tumor is a perihilar cholangiocarcinoma that occurs within 2 cm of the confluence of the right and left hepatic duct at the hepatic hilum and accounts for 50–70% of all cholangiocarcinomas cases. Although imaging techniques have come very far today, this entity can still be very challenging to diagnose as there are many lesions that can mimic Klatskin tumor. In this review, we will present the most common Klatskin-mimicking lesions.